Automation of the process of stepwise adjustment of pH and Eh parameters in the treatment of metal-containing wastewater - Fylypchuk, Leonid (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
The system of complex multistage control of process of sewage treatment from heavy metals by stepwise regulation of parameters Еh and pH is developed. Each of the control steps consists of a series of reagent dosing periods and a stabilization period. Reagent dosing is managed by local regulators, whose tuning parameters are determined for each step and adjustment period.